Cover Picture: Mn3TeO6 – a new multiferroic material with two magnetic sub‐structures (Phys. Status Solidi RRL 12/2015). Issue 12 (December 2015) - Zhao, Li; Hu, Zhiwei; Kuo, Chang‐Yang; Pi, Tun‐Wen; Wu, Maw‐Kuen; Tjeng, Liu Hao; Komarek, Alexander C.
Abstract : No abstract is available for this article. Abstract : Li Zhao et al. (pp.730‐734 ) report on multiferroic properties in Mn3 TeO6 . At low temperatures two successive magnetic transitions occur in this ortho‐tellurate. Ferroelectricity is induced below the second magnetic ordering temperature where a complex incommensurate spiral spin structure emerges which possibly consists of two different spin substructures – a helical and a cycloidal one. Both spin substructures might contribute to the electric polarization via different mechanisms. Hence, the discovery of multiferroicity in Mn3 TeO6 could open new ways of manipulating the ferroelectric polarization in a multiferroic material.